Makorin rings the kisspeptin bell to signal pubertal initiation. - Abbara,A; Dhillo,WS (Journal of Clinical Investigation, 2020)
The signals maintaining quiescence of the reproductive endocrine axis during childhood before its reawakening at puberty had been enigmatic. Studies in patients with abnormal puberty have illuminated the identity of the signals; kisspeptin has emerged as a major stimulator of puberty, and makorin RING finger protein 3 (MKRN3) as an inhibitory signal that prevents premature initiation of puberty. In this issue of the JCI, Abreu et al. investigated the mechanism by which MKRN3 regulates pubertal onset. The authors found that a reduction in MKRN3 alleviated the constraint on kisspeptin-expressing neurons to allow pubertal initiation, a phenomenon observed across species, including nonhuman primates. Further, the ubiquitinase activity of MKRN3 required its RING finger domain, in order to repress the promoter activity of genes encoding kisspeptin and neurokinin B. These data advance our understanding of the regulation of kisspeptin-expressing neurons by MKRN3 to initiate puberty.